Prospective observational study of vaginal microbiota pre‐ and post‐rescue cervical cerclage. (10th March 2019) - Brown, RG; Chan, D; Terzidou, V; Lee, YS; Smith, A; Marchesi, JR; MacIntyre, DA; Bennett, PR
Abstract : Objective: To investigate the relation between vaginal microbiota composition and outcome of rescue cervical cerclage. Design: Prospective observational study. Setting: Queen Charlotte's and Chelsea Hospital, London. Population: Twenty singleton pregnancies undergoing a rescue cervical cerclage. Methods: Vaginal microbiota composition was analysed in women presenting with a dilated cervix and exposed fetal membranes before and 10 days following rescue cervical cerclage and was correlated with clinical outcomes. Main outcome measures: Composition of vaginal bacteria was characterised by culture‐independent next generation sequencing. Successful cerclage was defined as that resulting in the birth of a neonate discharged from hospital without morbidity. Unsuccessful cerclage was defined as procedures culminating in miscarriage, intrauterine death, neonatal death or significant neonatal morbidity. Results: Reduced Lactobacillus spp. relative abundance was observed in 40% of cases prior to rescue cerclage compared with 10% of gestation age‐matched controls (8/20, 40% versus 3/30, 10%, P = 0.017). Gardnerella vaginalis was over‐represented in women presenting with symptoms (3/7, 43% versus 0/13, 0%, P = 0.03, linear discriminant analysis, LDA (log 10) and cases culminating in miscarriage (3/6, 50% versus 0/14, 0%, P = 0.017). In the majority of cases (10/14, 71%) bacterial composition was unchanged following cerclage insertion and perioperative interventions. Conclusions: Reduced relative abundance of Lactobacillus spp. is associated with premature cervical dilation, whereas high levels of G. vaginalis are associated with unsuccessful rescue cerclage cases. The insertion of a rescue cerclage does not affect the underlying bacterial composition in the majority of cases. Tweetable abstract: Preterm cervical dilatation associates with reduced Lactobacillus spp. Presence of Gardnerella vaginalis predicts rescue cerclage failure. Tweetable abstract: Preterm cervical dilatation associates with reduced Lactobacillus spp. Presence of Gardnerella vaginalis predicts rescue cerclage failure.